Deep sea ecosystem exploration and ‘health check’: sampling strategy and methods applied during the iAtlantic_BR10_Petrobras cruise in the Santos Basin, Southwest Atlantic (Ocean and Coastal Research, 2024)
The iAtlantic Project has established an international collaborative strategy to improve mapping andcharacterization of deep and open ocean ecosystems in understudied regions of the Atlantic and evaluatetheir health. In December 2022, the first iAtlantic expedition in the South Atlantic set off to map and exploreseafloor ecosystems in the Santos Basin slope (200-1,000 m depths) in collaboration with the Petrobras ‘SantosBasin - Regional Characterization Project.’ The 17-day ‘iAtlantic_BR10-Petrobras’ cruise was conducted onboard the research vessel NPqHOc Vital de Oliveira (Brazilian Navy) and performed (a) water column structurecharacterization, (b) seafloor morphology mapping, (c) description of benthic habitats and communities byseafloor imagery and biological/ geological sampling, and (d) ex-situ experiments to assess the functioning ofsedimentary ecosystems and their responses to climate-related environmental changes. This study describesthe rationale behind the iAtlantic_BR10-Petrobras cruise science plan, reports its sampling strategy andmethods, and summarizes its collected data and preliminary results.